STUDENTS' WHATSAPP LANGUAGE POLITENESS ATTITUDES MESSAGES to LECTURER at AL-QOLAM MALANG - M. Odik Afifin (Jurnal Inovatif Manajemen Pendidikan Islam, 2022)
This research aims to determine language politeness in communicating via WhatsApp between students and lecturers. The research methodology used is descriptive qualitative with a research focus on the language style and the principle of politeness in WhatsApp using based on the ethics of sending messages. Data were collected using documentation and data analysis techniques with a normative method approach. The results of the investigation of this study indicate that the language style of students towards lecturers tends to ignore the correct language structure rules. In terms of the lexical aspect, a mixture of formal language and slang is still common. However, in communicating based on the social network, WhatsApp, some students have been able to meet the ethics of sending messages by paying attention to the principle of language politeness. Even so, there were also several messages sent by other students that contained violations of politeness to communicate based on media messages WhatsApp.